Pengembangan Media Kartu Uno Berbasis Kearifan Lokal dalam Materi Tanda Baca untuk Murid Kelas IV di SD Negeri 3 Suranadi - Sutrisna Jumhari; Muhammad Tahir; Syarifuddin (Mataram University, 2026)
The mastery of punctuation material among fourth-grade elementary school students is often hindered by monotonous learning media and less meaningful learning processes. This condition requires innovative learning media that can facilitate student engagement and integrate local wisdom to create contextual and meaningful learning experiences. This study aimed to develop a local wisdom-based Uno card learning media for punctuation material and to examine its quality in terms of validity, practicality, and effectiveness. The research employed the Research and Development (R&D) method using the ADDIE model. The research subjects consisted of expert validators, 33 fourth-grade students, and the fourth-grade homeroom teacher of SD Negeri 3 Suranadi. Data collection instruments included validation sheets, student and teacher response questionnaires, and tests. The data analysis techniques used were descriptive validity analysis, descriptive practicality analysis, normality test, Paired Sample T-Test, and N-gain test. The results showed that the Uno card media and supporting books were successfully developed, with material validity reaching 92.5%, language validity 82%, and media validity 92.8%, all categorized as Very Valid. The study also indicated that the media was highly practical, with student response percentages reaching 89.6% and teacher responses 95%. The N-gain test result obtained a percentage of 60.67%, categorized as Moderately Effective. Therefore, the local wisdom-based Uno card media is considered very valid, highly practical, and moderately effective for learning activities.